Extraction of a Homogeneous Rhodium Catalyst from Saturated Branched Fatty Derivatives. Issue 6 (22nd April 2016) - Haßelberg, Jennifer; Behr, Arno; Herden, Nathalie; Drescher, Daniel
Abstract: Saturated branched fatty derivatives are of great interest for the lubricants and cosmetics industry due to their improved temperature and viscosity behavior compared to the corresponding linear homologues. One way to produce saturated branched derivatives is the homogeneous rhodium‐catalyzed conjugation and co‐oligomerization of linoleic compounds based on renewable resources, e.g., sunflower oil, with ethene. The catalyst extraction behavior of the homogeneous rhodium catalyst RhCl3 ·3H2 O from saturated branched fatty derivatives for catalyst recycling was studied. Investigation of the extraction parameters was performed using the model substance isostearic acid. Additionally, extraction of rhodium from co‐oligomer mixtures with different grade of saturation was carried out successfully. Also, the influence of solvent residues from prior reaction steps was evaluated. Abstract : Branched fatty derivatives possess huge potential for the cosmetics or lubricants industry. An example for a commercially available product is isostearic acid. Co‐oligomers of linoleic compounds and ethene represent higher branched products produced by homogeneous rhodium catalysis. Rhodium extraction from such branched derivatives is proposed as a possible catalyst recycling method.